Religion and Human Rights : An International Perspective - Ziebertz, Hans-Georg; Črpić, Gordan (Springer International Publishing : Imprint: Springer, 2015)
This book examines the relationship between human rights and religiosity. It discusses whether the impact of religiosity on human rights is liberational or suppressive, and sheds light on the direction in which the relationship between religion and human rights is expected to develop. The questions explored in this volume are: Which are the rights that are currently debated or under pressure? What is the position on human rights that churches and religious communities represent? Are there tensions between churches, religious communities and the state? Which rights are especially relevant for young people and which relate to adolescents life-world experiences? Covering 17 countries, the book describes two separate, yet connected studies. The first study presents research by experts from individual countries describing the state of human rights and neuralgic points anticipated in individual societies. The other study presents specific findings on the relationship between these two social phenomena from empirical research in a population of high school students. Studying this particular population allows insights into social trends, value systems and attitudes on human rights, as well as an indication of the likely directions of development, and potential room for intervention.